Type 2 diabetes mellitus in children and adolescent: an Indonesian perspective - Aman Bhakti Pulungan; Ireska Tsaniya Afifa; Diadra Annisa (Korean Society of Pediatric Endocrinology, 2018)
The prevalence of type 2 diabetes mellitus (T2DM) in children and adolescents has increased globally over the past 2 decades. Metabolic syndrome, including obesity and overweight at a young age, increases the occurrence of T2DM. Studies in Indonesia have found that obese children and adolescents are more likely to have insulin resistance, a risk factor for T2DM. There are no data on the current incidence of T2DM in youth in Indonesia, but there has been a significant rise in the prevalence of overweight in adolescents. The diagnosis of T2DM in youth is similar to that in adults, with special consideration of when to test asymptomatic children. Management of T2DM in Indonesia follows the recommendations of the Indonesian Pediatric Society, which include lifestyle modifications, such as improving dietary habits and exercise, as well as appropriate medications. Metformin is the drug of choice for young T2DM patients; if marked hyperglycemia is present, basal insulin is given with metformin. Monitoring of T2DM is generally done through selfmonitoring of blood glucose and glycosylated hemoglobin.